"Male Delivery": a critical investigation of what boys have to say about the influence of male teachers on literacy engagement and achievement. Issue 1 (1st January 2017) - Watson, Anne
Abstract: This article, by drawing on data collected from qualitative case-study research, raises questions about discourses that claim male teachers are better equipped to improve boys' literacy achievement on the basis of gender affiliation. It reports on interview and observational data collected from a number of boys attending five different secondary-schools in Ontario, Canada. It strategically draws on Connell's critical masculinities theoretical perspective and Foucault's analytic framework for power/knowledge, subjectivity and discourse, as a basis for producing a more nuanced understanding of commonly-accepted beliefs about the potential influence of male teachers to improve boys' engagement and achievement as literacy learners. This research found that only four of the 29 boys who participated in this study understand the gender of their teachers to be a critical factor for their engagement and achievement. Their narratives draw attention, not only to the complex and multiple factors influencing engagement and achievement, but also to the way in which power/knowledge and gender regimes influence their articulation of teacher influence. The findings of this research suggest that building more nuanced theories about teacher influence that move beyond so-called "common-sense" assumptions about role modeling and gender affiliation is critical if effective school reforms to address boys' literacy achievement are to be implemented.